2022
DOI: 10.1002/mcf2.10195
|View full text |Cite
|
Sign up to set email alerts
|

Economic Values of Potential Regulation Changes for the Southern Flounder Fishery in Louisiana

Abstract: Population declines of Southern FlounderParalichthys lethostigma have reached levels that present management concerns in Louisiana waters. As the need for regulatory change in this fishery approaches, we conducted a survey to better characterize the Southern Flounder fishery in Louisiana, with two primary goals: (1) determining a value for the economic welfare provided by the fishery and (2) evaluating how this value might change in response to hypothetical regulation scenarios. Based on total travel cost esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…estimates of (n = 1,136) coastal Louisiana recreational anglers reported an average one-way distance for a fishing trip to be 86 miles [33], which would keep most anglers fishing within the region that they live.…”
Section: Plos Onementioning
confidence: 99%
“…estimates of (n = 1,136) coastal Louisiana recreational anglers reported an average one-way distance for a fishing trip to be 86 miles [33], which would keep most anglers fishing within the region that they live.…”
Section: Plos Onementioning
confidence: 99%
“…However, a recent study that asked anglers how many trips they would take under hypothetical Louisiana Southern Flounder Paralichthys lethostigma regulation alternatives, including different bag (creel) limits, found that “the regulations presented in the survey would not significantly alter general angling behaviors or the economic values provided by coastal Louisiana angling” (Smith et al. 2022:9). Similarly, another recent study of the U.S. East Coast Striped Bass Morone saxatilis fishery found that while most anglers would not change their effort in the face of hypothetical bag limit increases, the share of anglers who said that they would increase their effort was twice the share of anglers who said that they would decrease their effort for the same bag limit increase (Murphy et al.…”
mentioning
confidence: 99%